2016
DOI: 10.1038/srep21907
|View full text |Cite
|
Sign up to set email alerts
|

A mirror code for protein-cholesterol interactions in the two leaflets of biological membranes

Abstract: Cholesterol controls the activity of a wide range of membrane receptors through specific interactions and identifying cholesterol recognition motifs is therefore critical for understanding signaling receptor function. The membrane-spanning domains of the paradigm neurotransmitter receptor for acetylcholine (AChR) display a series of cholesterol consensus domains (referred to as “CARC”). Here we use a combination of molecular modeling, lipid monolayer/mutational approaches and NMR spectroscopy to study the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 52 publications
7
144
0
Order By: Relevance
“…This computational finding was challenged by physicochemical lipid monolayer studies using a CARC-carrying peptide and cholesterol. The fact that the F-452/W mutation had no effect led us to suggest that it is the aromatic nature of Phe-452, and not its specific structure, that is required for optimal binding [47], in agreement with previous studies suggesting that CARC motifs could contain any of the three aromatic residues, i.e. Phe, Trp or Tyr [8,49].…”
Section: Identifying Cholesterol-recognition Motifs In Membrane Proteinssupporting
confidence: 70%
See 4 more Smart Citations
“…This computational finding was challenged by physicochemical lipid monolayer studies using a CARC-carrying peptide and cholesterol. The fact that the F-452/W mutation had no effect led us to suggest that it is the aromatic nature of Phe-452, and not its specific structure, that is required for optimal binding [47], in agreement with previous studies suggesting that CARC motifs could contain any of the three aromatic residues, i.e. Phe, Trp or Tyr [8,49].…”
Section: Identifying Cholesterol-recognition Motifs In Membrane Proteinssupporting
confidence: 70%
“…NMR spectroscopy experiments (MAS triple resonance magic-angle spinning deuterium NMR using deuterated Ala471) [47] showed that cholesterol addition to phospholipid bilayers containing a synthetic 13C/15N-labeled peptide (Asp464-Val492 in the intact Torpedo γ TM4) caused a reduction in the rotational motion of the peptide within the bilayer, further reinforcing the cholesterol-mediated peptide oligomerization hypothesis. It is tempting to extrapolate the results of the isolated peptide experiments to the possible role of the CARC domains in situ, where they could play a role in cholesterolmediated oligomerization of the receptor.…”
Section: Fj Barrantes / Cholesterol-receptor Interactionsmentioning
confidence: 68%
See 3 more Smart Citations